India’s Fifth-Generation Warfare against Pakistan and the Role of Indian Media in Shaping Public Perceptions of the China-Pakistan Economic Corridor (CPEC) (Journal of Social Sciences Review, 2025)
The China-Pakistan Economic Corridor (CPEC) has become a catalyst for South Asian geopolitics, particularly in the information war between India and Pakistan. In this context, this study critically analyses how Indian and Pakistani media shape public perceptions of CPEC by creating different narratives that serve their national interests. The Pakistani media portrays CPEC as a transformative economic initiative that promotes development and regional connectivity, while the Indian media frames it as a geopolitical threat that raises sovereignty concerns and increases China's economic and strategic influence in the Indian Ocean. In addition, this study analyses news items, TV shows, talk shows, social media trends, and hashtags. This study highlights how traditional and social media impact public opinion. According to the study, state-sponsored narratives, misinformation campaigns, and strategic media framing polarise discourse, emphasizing nationalistic sentiments that align with India's national interest against CPEC, the Belt and Road Initiative's flagship project. Additionally, social media's revolutionary role strengthens these narratives, entrenching popular perceptions diplomatic escalations, and harsh words. This study emphasizes the media's influence on geopolitical discourse and information warfare's effects on regional stability. Finally, the study urges both sides to improve media literacy and journalism to combat misinformation and better grasp CPEC's economic and strategic aspects.
Keywords: 5GW; CPEC; Media; Public Opinion; Geopolitics; Warfare